2017
DOI: 10.1177/1471301217714654
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Changes in Dementia and their Impact on Professional Caregivers: A Grounded Theory Approach

Abstract: Aim: The present study aimed to explore the impact that changes in behavioural symptoms of people living with dementia have on professional caregiver and resident relationships. Method: A total of 21 interviews were carried out with professional caregivers of people living with dementia. A grounded theory approach was used to investigate everyday experiences of provision of professional care in dementia settings, focussing specifically on the effect of behavioural change on such relationships. Results: A core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The present study revealed that sensor information was perceived to enhance continuity in care and improve the staff's understanding of the individual with dementia and their needs, since it contributed to the information collected over time. An enhanced understanding of needs has been shown to strengthen the relationship between the nursing staff and the individual with dementia [ 36 ], which has been identified as one of the most influential factors in caregiving satisfaction [ 37 ] and shown to affect the well-being of individuals with dementia [ 38 ]. Based on the present findings, we suggest that information from an EDA sensor can contribute to an improved assessment process with enhanced recognition and understanding of an individual's needs, which, in turn, can improve nursing staff's work satisfaction [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that sensor information was perceived to enhance continuity in care and improve the staff's understanding of the individual with dementia and their needs, since it contributed to the information collected over time. An enhanced understanding of needs has been shown to strengthen the relationship between the nursing staff and the individual with dementia [ 36 ], which has been identified as one of the most influential factors in caregiving satisfaction [ 37 ] and shown to affect the well-being of individuals with dementia [ 38 ]. Based on the present findings, we suggest that information from an EDA sensor can contribute to an improved assessment process with enhanced recognition and understanding of an individual's needs, which, in turn, can improve nursing staff's work satisfaction [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variability may be related to the varying level of adherence to the intervention by the individual caregivers, which might reflect the difficulties for caregivers working in SCU to change their accustomed behaviour in their daily work. Caregiver training should focus on more intense and in-depth training to increase the understanding of behavioural change across the development of dementia [ 35 ]. Genuine professional knowledge concerning the fundamental needs in persons with dementia is recognized as crucial in caregivers for dyadic interactions in dementia care [ 36 , 37 ], which means that health care professionals need to recognize the perspectives of both parts since the PwD needs to rely on the other’s contributions in the interaction [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variability may be related to the varying level of adherence to the intervention by the individual caregivers, which might re ect the di culties for caregivers working in SCU to change their accustomed behaviour in their daily work. Caregiver training should focus on more intense and in-depth training to increase the understanding of behavioural change across the development of dementia (Appleton & Pereira, 2019). Genuine professional knowledge concerning the fundamental needs in persons with dementia is recognized as crucial in caregivers for dyadic interactions in dementia care (Jakobsen & Sørlie, 2010;Manthorpe et al, 2010), which means that health care professionals need to recognize the perspectives of both parts since the PwD needs to rely on the other's contributions in the interaction (Lichtner et al, 2016).…”
Section: Discussionmentioning
confidence: 99%